Rancang Bangun Sistem Informasi Aset Elektronik Prusahaan Berbasis Website - Donny Muda Priyangan; Adik susilo wardoyo; Rizal Ridowardana (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2026)
The rapid development of information technology (IT) has encouraged various industrial sectors to adopt digitalization to improve efficiency and productivity. PT. TKP, a Mining company in Indonesia, faces challenges in the manual maintenance and monitoring process that makes monitoring ineffective and prone to errors. This study aims to overcome these problems by designing and building an electronic website-based asset information system. This digitalization process is expected to reduce ineffectiveness when monitoring assets, facilitate asset maintenance scheduling, and improve operational efficiency. The methods used include application modeling using the CodeIgniter framework and the PostgreSQL database. The results of the study show that digitalization and the use of information technology can improve efficiency and effectiveness in data management. The implementation of this system is expected to bring significant improvements in the production process of PT. TKP and provide broader benefits in the manufacturing industry